Health Implications of Using Euphorbia hirta Linn. (Euphorbiaceae) Extracts in the Treatment of ‘Jedi Jedi’ Infection in Newborns (Age one to six months) in Nigeria - UKWUBILE, Cletus Anes (Pharmacognosy Communications)
Objective: To determine the effects of the crude extracts of Euphorbia hirta in treating ‘Jedi Jedi’ infection in newborns, in Nigeria. Materials and Methods: The powdered plant material of Euphorbia hirta was extracted in three solvents ethanol, benzene and water using the Soxhlet extraction apparatus 241 (PSAWINDIA). Phytochemical screening was conducted to determine the plant constituents, while acute and chronic toxicity studies were carried out in vivo using nine albino mice. Results: The percentage yields of the extracts were 59 (water), 33 (ethanol), and 16 (benzene). Phytochemical screening of the crude extracts revealed the presence of saponins, fl avonoids, cardiac glycosides, cyanogenic glycosides, anthraquinones, and alkaloids. The presence of these constituents was linked to the antibacterial activity of the plant, using the agar well-diffusion method against bacteria associated with ‘Jedi Jedi’ infection, namely, Escherichia coli, Bacillus subtilis, Proteus mirabilis, Salmonella typhi, Pseudomonas aeruginosa . The minimum inhibitory concentration (MIC) of the extracts of E. coli, B. subtilis, P. mirabilis, S. typhi , and P. aeruginosa were 50 mg/ml, 25 mg/ml, 50 mg/ml, 25 mg/ml, and 25 mg/ml respectively. Toxicity studies revealed that most of the animals were adversely affected on long-term usage of the plant extracts, leading to the death of some of the animals while short-term usage produced organ infl ammation, hypertrophy, ulcers and necrosis of some organs. Conclusion: Although these bacteria were susceptible to the extracts in various solvents that were signifi cantly different from the control drug Cefuroxime Axetil® USP 100 ml (Bharat Parenterals Ltd., India) (p ≤ 0.05), the results suggested that the use of the extracts of E. hirta as an oral medication, both on short -term and long-term was not safe, due to the presence of some toxic constituents.
Keywords: Benzene extract; Ethanol extract; Euphorbia hirta; Infection; phytochemical; toxicity; water extract